Case Study of Islamic Religious: The Influence of Islamic Religious Guidance on the Practice of Prayer at Madrasah - Abidin, Aji; Mohammed, Marwa Jassim; Siahkoohian, Hatef (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2024)
Purpose of the study: This research aims to determine the influence of Islamic religious formation on the prayer practice of madrasah children. Islamic religious formation in children has a big positive impact on the practice of prayer. Methodology: This research is a type of quantitative research. carry out research by distributing questionnaires and rating scales, because in this case the observations use a rating scale. Respondents numbered 30 madrasah children. Then, to obtain data about the development of the Islamic religion and the implementation of prayer services by children, a questionnaire and rating scale were used. Main Findings: Islamic religious formation has a significant influence on the practice of prayer. Through these coaching efforts, individuals gain a deep understanding of Islamic teachings, including the procedures for performing prayers. Religious formation can strengthen spiritual beliefs and awareness, motivating individuals to perform prayer services consistently. Understanding of the meaning and purpose of prayer can also be improved through religious formation, so that individuals feel a closer connection with Allah in every prayer movement. Novelty/Originality of this study: The importance of the development of the Islamic religion in forming the spiritual awareness of the people has a significant positive impact on the intensity and quality of the prayer practice of madrasah children. By focusing on a deep understanding of Islamic teachings, this training is the main key in forming individuals who are devout and devout in worship.